Biomimetic electro-oxidation of alkyl sulfides from exfoliated molybdenum disulfide nanosheets. Issue 47 (17th November 2020) - Maachou, Lahcene; Qi, Kun; Petit, Eddy; Qin, Zhaodan; Zhang, Yang; Cot, Didier; Flaud, Valérie; Reibel, Corine; El-Maghrbi, Heba; Li, Lei; Miele, Philippe; Kaplan, Daniel; et al.
Abstract : High electrocatalytic performance of biomimetic exfoliated molybdenum disulfide nanosheets towards the electro-oxidation of alkyl sulfides. Abstract : Enzymes are biological catalysts that are interesting for key reactions such as hydrogen evolution, CO2 conversion into hydrocarbons and the fixation of nitrogen. Enzymes are particularly good catalysts for organic reactions because of their high selectivity. However, they exhibit modest stability and require extensive purification, which makes them costly. Here, we report a biomimetic electroactive two-dimensional (2D) catalyst based on single-layer metallic MoS2 nanosheets for the oxidation of alkyl and aryl sulfides. The structure of the MoS2 nanosheets mimics the active site of natural dimethyl sulfoxide (DMSO) reductase found in anaerobic bacteria. We demonstrate that 2D MoS2 nanosheets efficiently oxidize organic sulfides. Notably, we show that dimethyl sulfide can be electro-oxidized to DMSO with activity surpassing that of noble metal catalysts. The production of DMSO using metallic 1T′ phase MoS2 reaches 680 L per h per gram at 1500 mV vs. NHE – ∼4 times higher than platinum nanoparticles – and is stable for >24 hours. Our findings provide new directions for electrosynthesis from metallic 2D materials.